MAKNA SIMBOL ANDUNG (RATAPAN) DALAM UPACARA PEMAKAMAN ADAT BATAK TOBA DI PEKANBARU - Flora, Hotmaida; Tinambunan, W.E (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The Meaning of Symbols in Funeral Customs Batak Toba in Pekanbaru. Cultural is a skill which  owned by a group of people to recognize, interpret, and produce signs with the someway. Every culture has a certain characteristics, from the event or ritual that uccurs while the ceremony took place. Culture became the most important thing, because of identity that shows of the character of every person who owns it. Consequently, culture is the foundation of communication. When diverse cultures, it’s also diverse practice of communication.Toba society is a society that respect customany norms inherited by  ancestor to them abo ut nuptial as well as funereal ceremony. They prove about loyalty on the customany practice with division of big energy to Toba society customany practice, particulary about andung at funereal ceremony.Andung is lamentation or funereal song on funeral or misfortune. Generally, andung contains about sadness or suffering life. From of misfortune are sadness and grief when parents, family members died. This is a lamentation song in Batak Toba people, content of andung is about life stories of people who died and song in front of his body. While do andung, people who came absolutely know about his character during his lifetime. Andung is one of cultural heritage that ever lived and powerful role in Batak Toba society that still used to this day. Only a certain parents can mastering hata andung and only those who can performing it with use hata andung properly.Because phenomena happened in funeral customs on Batak Toba society, so author can take this thesis with the title “ The Meaning of Symbols in Funeral Customs Batak Toba in Pekanbaru”.Keyword : Andung, The meaning of symbols, Funeral